Incidence of upper limb venous thrombosis associated with peripherally inserted central catheters (PICC). - Abdullah, B.J.J.; Mohammad, N.; Sangkar, J.V.; Abd Aziz, Y.F.; Gan, G.G.; Goh, K.Y.; Benedict, I. (British Institute of Radiology, 2005)
The objective of this study was to prospectively determine the incidence of venous thrombosis (VT) in the upper limbs in patients with peripherally inserted central catheters (PICC). We prospectively investigated the incidence of VT in the upper limbs of 26 patients who had PICC inserted. The inclusion criteria were all patients who had a PICC inserted, whilst the exclusion criterion was the inability to perform a venogram (allergies, previous contrast medium reaction and inability of gaining venous access). Both valved and non-valved catheters were evaluated. Prior to removal of the PICC, an upper limb venogram was performed. The number of segments involved with VT were determined. The duration of central venous catheterization was classified as; less than 6 days, between 6 days and 14 days and more than 14 days. VT was confirmed in 38.5% (10/26) of the patients. The majority 85.7% (12/14) were complete occlusive thrombi and the majority of VT only involved one segment. There was no statistical correlation between the site of insertion of the PICC and the location of VT. Neither was there any observed correlation between the occurrence of VT with the patient's history of hypertension, hypercholesterolaemia, coronary artery disease, diabetes mellitus, cardiac insufficiency, smoking or cancer. There was also no statistical correlation with the size of the catheter. In conclusion, PICCs are associated with a significant risk of upper extremity deep vein thrombosis (UEVT).